การขยายพันธุ์ในสภาพปลอดเชื้อหญ้าพันเกลียว (Ceropegia thailandica Meve) พืชใกล้สูญพันธุ์อย่างยิ่งในประเทศไทย - ศรีปฐมกุล เกศินี; เทียนหอม อารยา อาจเจริญ; จารุวัฒนพันธ์ ทัศไนย (Thai Journal of Science and Technology, 2019)
Ceropegia thailandica Meve is endemic and critically endangered. Plant tissue culture is the efficient method for ex situ conservation. This study aims to find a suitable method for in vitro propagation of C. thailandica. Nodal segments were sterilized with four different surface sterilization methods and cultured on MS medium for 5 weeks. The result showed that the explants sterilized with 0.3 % (v/v) NaOCl for 10 minutes followed by 0.2 % (w/v) HgCl2 for 5 minutes had the lowest contamination rate (40 %) and the highest survival rate (26.66 %). Effect of BA and Kn on shoot and tuber induction from nodal segment was studied. Nodal segments were cultured on MS medium supplemented with different concentrations of BA and Kn (0, 0.5, 1.0, 1.5, 2.0 or 2.5 mg/L) for 8 weeks. The result showed that the best shoot induction (15.80 shoots) was found in MS medium supplemented with 2 mg/L BA, and the best tuberization (87 %) was found in MS medium supplement with 2.5 mg/L Kn. Regenerated shoots of C. thailandica were cultured on MS medium supplemented with different concentrations of IBA and NAA (0, 0.5, 1.0, 1.5 2.0 or 2.5 mg/L) for 8 weeks to observed root induction. The results showed that 0.5 mg/L IBA had the highest root induction (3.60 roots), and at all concentrations IBA and 1.5 mg/L NAA gave the highest callus induction (100 %)